(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current state of work motivation of nurses at Ninh Binh General Hospital in 2023. Methods: Cross-sectional descriptive study was conducted from July 2023 to December 2023 on 244 nurses working at Ninh Binh General Hospital. The reference toolkit for measuring nurses’ work motivation from previous studies was revised, evaluated by experts, and tested before use. Analyze and process data using SPSS 20 with tables describing frequencies and proportions. Results: 61.9% of nurses were motivated by commitment to the organization, 75.4% were motivated by the nature of the work, 58.2% were motivated by the benefits of work, 55.3% were motivated by relationships at work, and the rate of nurses who are motivated to work in general is 75.4%. Conclusion: From the results of this research, hospitals need to focus on good motivational factors and improve low motivational factors to increase nurses’ work motivation, thereby improving service quality. health and patient satisfaction.